Use of clinical simulation to improve diagnostic reasoning in nursing - Ingrid Régia Lopes Jerônimo; Juliana Faria Campos; Mauricio Abreu Pinto Peixoto; Marcos Antônio Gomes Brandão (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objectives: Propose a methodology for the construction of simulated scenarios and cases to improve diagnostic reasoning in nursing. Method: A methodological study was conducted using theories and concepts from the dual processing theory to develop cases and scenarios of clinical simulation for diagnostic reasoning in nursing through proper use of analytical and non-analytical reasoning. Results and discussion: This study presents and discusses issues of the theoretical framework and operational elements: structure of scenarios, preparation of simulation, briefing, debriefing, and modeling, incorporating any required content. The methodology articulates content that is compatible with analytical reasoning, non-analytical studies and diagnostic accuracy measurements of clinical validation studies. Conclusion: This study demonstrated the feasibility of modeling simulated cases that combine dual processing with diagnostic reasoning in nursing. Implications: Contribution to learning in a safer simulated environment, adopting theoretical bases from studies on human reasoning.